2017
DOI: 10.4309/jgi.v0i35.3971
|View full text |Cite
|
Sign up to set email alerts
|

Financial recovery from problem gambling: problem gamblers’ experiences of social assistance and other financial support

Abstract: The objective of this article is to understand problem gamblers' experiences of recovery from financial difficulties caused by problem gambling. Specifically, financial social assistance from public services is considered. A sample of 17 interviews with Finnish self-identified, treatment-seeking problem gamblers from various financial positions was analyzed qualitatively using thematic content analysis. The analysis revealed four themes. The first theme examines how the financial concerns of problem gamblers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The interviews had a social approach in that the questions concentrated on the everyday lives, relationships, and environments of the gamblers. Other aspects of the same data, mainly financial recovery from problem gambling, are reported in other analyses ( Heiskanen, 2017 ).…”
Section: Methodssupporting
confidence: 57%
“…The interviews had a social approach in that the questions concentrated on the everyday lives, relationships, and environments of the gamblers. Other aspects of the same data, mainly financial recovery from problem gambling, are reported in other analyses ( Heiskanen, 2017 ).…”
Section: Methodssupporting
confidence: 57%
“…Previous Finnish research has shown that while people with high incomes would spend larger sums on gambling, it was people with lower incomes who would use larger amounts for gambling when the sums were viewed as relative amounts of incomes ( Castrén, Kontto, Alho, & Salonen, 2017 ; Salonen, Kontto, Alho, & Castrén, 2017 ). Gambling can be an effort to solve economic problems, and for problem gamblers a new chance of winning back money may seem like the only way out of considerable debts ( Heiskanen, 2017 ). Mapping the reasoning behind different types of gambling provides valuable knowledge for the planning of help provision.…”
Section: Discussionmentioning
confidence: 99%
“…Stress created by gambling problems is a further possible explanation for why gambling might lead to violent acts. Financial stress typically increases with escalating gambling losses, depleting funds for household necessities, and sometimes leading to the sale of family assets and increased debt ( Patford, 2009 ; Browne et al, 2016 ; Heiskanen, 2017 ). Gamblers can also face emotional stresses arising from financial and relationship tensions, and can feel ashamed, hopeless, and guilty about their gambling ( Saugeres et al, 2012 ; Hing et al, 2020 ).…”
Section: Dfv/ipv Linked To a Perpetrator’s Gamblingmentioning
confidence: 99%